Die Regesten des Kaiserreiches unter Friedrich I., Lief.5 - Opll, Ferdinand (2018)
With the last volume of the "Regesta Imperii under Frederick I" a project started in 1975 has come to its end. Thereby the whole existing sources concerning the period and the reign of Frederick Barbarossa are encompassed and made accessible by an index of proper names and a bibliography.